On applicability of Frontier Regression to nowcast surface meteorological parameters at Chennai and Trichy airports in Tamilnadu - SURESH, R.; CHANDRA , K. SURESH; SIVAGNANAM, N. (MAUSAM, 2000)
An advanced statistical forecasting technique, viz., Frontier regression (FR) has been explored to augment the forecasting capacity in nowcasting of meteorological parameters for aviation flight planning at Chennai airport. As maritime effects strongly influence weather over a coastal station like Chennai, the model contemplated in this study has been tried for an inland airport station, viz., Trichy also to assess its efficacy.